Screened Potential by Electron Gas - Soghmonyan, A. I.; Mkhitaryan, S. A.; Markosyan, J. P.
Donors and acceptors in semiconductors are charged impurities with a Coulomb potential and, therefore, are screened by free charge carriers – electrons. An analytical description of the oscillations of the screened external potential by the electron gas is considered in this paper. Using the inverse transformation of the Fourier component, the screened Coulomb Potential U(r) and the value of the screening radius rs for the degenerate and nondegenerate electron gas are found. The dependence of rs on potentials is also given. It is shown that the screening radius decreases with increasing the electron density.
Keywords: Physics